2020
DOI: 10.3390/su12083337
|View full text |Cite
|
Sign up to set email alerts
|

The Role of Information Systems in the Sustainable Development of Enterprises: A Systematic Literature Network Analysis

Abstract: Information Systems (IS) play an important role in improving the efficiency of firms’ operations and supply chains, which links to sustainability. Therefore, this study conducted a systematic literature network analysis to review 132 articles that discuss current trends in the IS discipline. Based on a citation network analysis, this study discovered three main research domains (sustainable competitive advantage, environmental sustainability, and sustainable online social communities), and two emerging researc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 40 publications
(25 citation statements)
references
References 176 publications
(318 reference statements)
2
23
0
Order By: Relevance
“…Xu et al revealed the characteristics of China and India's sustainable advantages and clarified that China and India have different impacts on the imports of related fields in the United States [3]. Zeng et al proposed that the role of information systems was played in developing countries and sustainable information infrastructure [4]. Feng et al pointed out that if innovation and scientific research continuing in the high-tech industry, enterprises would maintain a competitive advantage [5].…”
Section: Introductionmentioning
confidence: 99%
“…Xu et al revealed the characteristics of China and India's sustainable advantages and clarified that China and India have different impacts on the imports of related fields in the United States [3]. Zeng et al proposed that the role of information systems was played in developing countries and sustainable information infrastructure [4]. Feng et al pointed out that if innovation and scientific research continuing in the high-tech industry, enterprises would maintain a competitive advantage [5].…”
Section: Introductionmentioning
confidence: 99%
“…This, in turn, would lead to enhancing decision-making processes within organizations. Against this background, IS adoption helps organizations bolster their economic sustainability and develop a sustainable competitive advantage [2]. This explains why tourism organizations invest much effort, and money to adopt IS.…”
Section: Introductionmentioning
confidence: 99%
“…[38]. Time management, cost over-runs, safety, quality management, customer value management, safety issues, and other business metrics and processes can be improved in a sustainable way through the application of ISs [39,40]. From here, the first hypothesis is proposed: Hypothesis 1 (H1).…”
Section: Information Systems and Sustainable Business Performance And Competitivenessmentioning
confidence: 99%